Product delivery service provider selection and customer satisfaction in the era of internet of things: a Chinese e-retailers’ perspective - YU, Jie; Subramanian, Nachiappan; Ning, Kun; Edwards, David (Elsevier, 2015)
In this study we focus on how e-retailers who deal with innovative products in the era of the Internet of Things (IoT) select product delivery service providers to ensure timely and efficient delivery to customers. Based on the asset–process–performance framework, we propose a triadic model that includes e-retailers, product delivery service providers and customers to achieve synergy and customer satisfaction in the era of the IoT. We find that substantive selective criteria should include consideration of product delivery service providers’ hard and soft infrastructure. In addition, flexibility is a key criterion that will strengthen the relationship between e-retailers and product delivery service providers to improve the competitiveness of e-retailers as well as to satisfy the customers. We validate the model using data from 148 Taobao e-retailers. Our results indicate that both hard and soft infrastructures have positive influence on flexibility which in turn has a positive impact on customer satisfaction. Indeed, flexibility fully mediates the relationship between hard and soft infrastructures and customer satisfaction. Our theoretical triadic model is one of the first attempts in providing product delivery service providers selection criteria for e-retailers selling innovative products and its influence on customer satisfaction. Our findings provide guidelines for both e-retailers and product delivery service providers to improve their competitiveness.